Effectiveness of Problem-Based Learning with Dr Stone Animation on Grade XI Students’ Acid-Base Learning Outcomes - Jannah, Miftahul; Tiwow, Vanny M. A.; Abram, Paulus H.; Nurmayanti, Yuli (Universitas Tadulako, 2025)
The background of this research is low student performance in the topic and the need for an innovative, interactive, and contextual learning approach. This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model using Dr Stone's animation media on students' learning outcomes in the acid-base topic for Grade XI students at SMA Negeri 1 Sirenja. The problem addressed in this research relates to how to improve student learning outcomes and engagement through the integration of contextual and technology-based media. The research employed a pre-experimental design with a one-group pre-test and post-test on a single experimental class consisting of 30 students. The instruments used included Lesson Plans (RPP), Student Worksheets (LKPD), Dr Stone animation media, and a multiple-choice learning outcome test consisting of 15 validated questions, reviewed and approved by expert validators. The validation results showed that all instruments were valid and appropriate for use. Student learning outcomes were analysed using the N-Gain score to measure the improvement after learning. The average N-Gain score was 0.7331 (73.31%), placing it in the moderately effective category. The average difference between pre-test and post-test scores was 37.10 points, indicating a significant improvement in student learning outcomes. Most students experienced substantial learning gains after participating in problem-based learning supported by animation media. This study demonstrates that combining the Problem-Based Learning (PBL) model with Dr Stone's animation media effectively improves student learning outcomes. Furthermore, this study supports the learning process by incorporating a contextual and interactive approach that fosters students’ motivation, deepens their conceptual understanding, and promotes active involvement in chemistry lessons. It also offers valuable guidance for teachers on applying technology-integrated, student-centred teaching strategies in science education.